A new species and synonymy in Elacatophora (Coleoptera, Staphylinidae, Scydmaeninae) - Jałoszyński, Paweł (Zootaxa, 2015)
A new species of the Oriental genus Elacatophora, E. euconnoides sp. n., is described from the Cameron Highlands, West Malaysia. Diagnostic characters, including the male genitalia, are illustrated and discussed. A new case of subjective synonymy was discovered: Elacatophora minae (Makhan & Ezzatpanah, 2011) is placed as syn. n. of E. soesilae (Makhan & Ezzatpanah, 2011).